Marxian Analysis - Beach, Earl F. (Relations industrielles / Industrial Relations, 1975)
The Marxian System [of economics] has been universally proclaimed to be dynamic. It is therefore of some importance to discover that the analytical framework is static, that it cannot be modified easily, and that it has led to a very wrong conclusion which has been embedded in Marxian thinking. –Author's introduction
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z